Conversion Reaction Mechanism for Yolk‐Shell‐Structured Iron Telluride‐C Nanospheres and Exploration of Their Electrochemical Performance as an Anode Material for Potassium‐Ion Batteries. Issue 10 (1st September 2020) - Park, Gi Dae; Kang, Yun Chan
Abstract: Various metal chalcogenide materials have been investigated as novel candidate anode materials for K‐ion batteries (KIBs). This pioneering study explores the electrochemical reaction between K‐ions and iron telluride. A detailed analysis is performed using in situ and ex situ methods, including X‐ray diffraction (XRD), X‐ray photoelectron spectroscopy (XPS), transmission electron microscopy (TEM), and cyclic voltammetry (CV), following the initial discharging and charging processes. The reversible reaction mechanism, from the second cycle of the reaction of FeTe2 with K‐ions, is 2Fe + K5 Te3  + K2 Te ↔ 2FeTe1.1  + 1.8Te + 7K +  + 7e ‐ . Hollow carbon nanospheres housing iron telluride nanocrystals (FeTe2 ‐C) are synthesized via facile infiltration and a one‐step tellurization process to compensate for the substantial volume change of nanocrystals during the potassiation and depotassiation processes. Excellent electrochemical properties arise from the synergistic effect of the heterointerfaced FeTe1.1 and metalloid Te formed after one cycle and the yolk‐shell architecture with uniformly distributed nanocrystals are embedded in a carbon shell. FeTe2 ‐C electrode demonstrates remarkable long‐term cycle performance (171 mA h g ‐1 for the 500th cycle at a high current density of 0.5 A g ‐1 ) and an excellent rate capability (126 mA h g ‐1 ), even at a high current density of 10 A g ‐1 . Abstract : In this study, a unique‐structured nanocomposite of iron telluride (FeTe2 ), and highly conductive carbon is successfully applied as a novel anode material for potassium ion (K‐ion) storage for the first time. Particularly, the conversion reaction mechanism of FeTe2 in K‐ion batteries is specifically investigated by using various in situ and ex situ measurements.